Case analysis of early-onset Alzheimer's disease associated with TBK1 p.Tyr235Phe gene mutation - Li, Pan; Y, Yuanyuan; Cai, Hao; Zhang, Huihong; Zhou, Yuying (Frontiers in Neurology, 2022)
TANK1-binding kinase 1 (TBK1) is mainly involved in the regulation of various cellular pathways through the autophagic lysosomal system, and the loss of function or hypofunction caused by TBK1 gene mutation mainly leads to frontotemporal lobar degeneration (FTLD), amyotrophic lateral sclerosis (ALS) and ALS-FTLD. Alzheimer disease (AD) due to TBK1 gene mutation is extremely rare, and only one case has been reported in China so far. In this report, we described a patient with early-onset AD (EOAD) in whom a new probable pathogenic variant c.704A>T (p.Tyr235Phe) in the TBK1 gene was identified by whole genome sequencing analysis. It is suggested that FTLD gene mutation may exist in patients with clinical manifestations of AD.